Cinderella (The Original Magical Story, 2017)
When their kingdom is trapped in an eternal winter, Anna sets off on a journey to find her sister, the Snow Queen Elsa. Can Anna and her new friends put an end to Elsa's icy spell and save Arendelle? Enjoy a classic Disney experience with this magical storybook, Disney Frozen The Original Magical Story.